A study to assess the outcomes following tonsillectomy in patients who were administered only prophylactic pre-operative antibiotics vis-à-vis patients who were administered both pre and post-operative antibiotics - Shah, Shikha; Thomas, James; Sonar, Tejal; Kancherla, Srinithya; Bhatnagar, Aastha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Tonsillectomy is one of the common operative surgery performed by an ENT surgeon. With aim to reduce the hospital stay and post-operative complications, the use of antibiotics has become every common. Methods: 40 patients undergoing tonsillectomy were recruited into the study subsequent to obtaining informed consent. The patients were divided in to two groups, group A and group B. Both the groups were given tablet amoxicillin with clavulanic acid orally for 3 days prior to surgery and subsequently were administered injection amoxicillin and clavulanic acid intravenously 1 hour prior to surgery pre operatively. Only group A patients were given injection amoxicillin and clavulanic acid intravenously 12 hourly for 5 days in the post-operative period. The patients from both the groups were assessed on the following criteria: pain, slough in the tonsillar fossa, fever, clot formation and return to normal daily activities. Results: Both the groups were comparable with regard to demographics, post-operative infections, post-operative pain and time to return to normal daily activities. There was no cognisant difference for all the parameters assessed. Conclusions: Administration of antibiotics in patients undergoing tonsillectomy can be restricted to pre-operative antibiotics only as giving antibiotics post-operatively does not affect the clinical outcome and also prevents indiscriminate use of antibiotics which can lead to mutant antibiotic resistant strains of bacteria which can also have an economic impact.